Plant biotechnology and genetics : principles, techniques, and applications - Stewart, C. Neal, Jr. (Hoboken, NJ : Wiley, 2008)
* Provides a thorough overview of botany and genetics for those students with minimal background in those areas, with coverage extending from very basic introductory materials to advanced techniques and applications. * Includes autobiographical essays from eminent scientists to provide insight into the field of plant biotechnology and how it is changing the face of agriculture. * Facilitates group discussions on problems and issues in plant biotechnology through the use of chapter questions and problems. * Includes a CD ROM with colour graphics to aid students and teachers in presenting and un.
Plant agriculture: the impact of biotechnology -- Mendelian genetics and plant reproduction -- Plant breeding -- Plant development and physiology -- Tissue culture: the manipulation of plant development -- Molecualr genetics of gene expression -- Recombinant DNA, vector design, and construction -- Genes and traits of interest for transgenic plants -- Marker genes and promoters -- Transgenic plant production -- Transgenic plant analysis -- Regulations and biosafety -- Field testing of transgenic plants -- Intellectual property in agricultural biotechnology: strategies for open access -- Why transgenic plants are so controversial -- The future of plant biotechnology.
Includes bibliographical references and index.
Print version record.
Keywords: Plant biotechnology; Plant genetics; Transgenic plants; Plant biotechnology; SCIENCE -- Biotechnology; Plant biotechnology; Plant genetics; Transgenic plants; Electronic books; Electronic books